2013
DOI: 10.6061/clinics/2013(sup01)08
|View full text |Cite
|
Sign up to set email alerts
|

Medical management of non-obstructive azoospermia

Abstract: Non-obstructive azoospermia is diagnosed in approximately 10% of infertile men. It represents a failure of spermatogenesis within the testis and, from a management standpoint, is due to either a lack of appropriate stimulation by gonadotropins or an intrinsic testicular impairment. The former category of patients has hypogonadotropic hypogonadism and benefits from specific hormonal therapy. These men show a remarkable recovery of spermatogenic function with exogenously administered gonadotropins or gonadotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 34 publications
(33 reference statements)
1
48
0
Order By: Relevance
“…Nonobstructive azoospermia is the most severe type of male infertility for many reasons, such as the correct diagnosis is unknown in at least half of cases; except for very specific situations, it is not possible to control or interfere with spermatogenesis; no preoperative tests can determine sperm retrieval rates; there is no better proven method to obtain spermatozoa from the testes; and the resulting pregnancy and delivery rates are heterogeneous and depend on testicular histology (Carpi, Sabanegh, & Mechanick, ; Kumar, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonobstructive azoospermia is the most severe type of male infertility for many reasons, such as the correct diagnosis is unknown in at least half of cases; except for very specific situations, it is not possible to control or interfere with spermatogenesis; no preoperative tests can determine sperm retrieval rates; there is no better proven method to obtain spermatozoa from the testes; and the resulting pregnancy and delivery rates are heterogeneous and depend on testicular histology (Carpi, Sabanegh, & Mechanick, ; Kumar, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonobstructive azoospermia is the most severe type of male infertility for many reasons, such as the correct diagnosis is unknown in at least half of cases; except for very specific situations, it is not possible to control or interfere with spermatogenesis; no preoperative tests can determine sperm retrieval rates; there is no better proven method to obtain spermatozoa from the testes; and the resulting pregnancy and delivery rates are heterogeneous and depend on testicular histology (Carpi, Sabanegh, & Mechanick, 2009;Kumar, 2013 of Sertoli cells, one of the causes of NOA, can be clinically suspected in cases of a high serum FSH level and small testes, but biopsy is the only way to confirm the diagnosis. Although hypergonadotropic hypogonadism is associated with poorer SSR outcomes, no study has reported it to be a predictive factor (Ishikawa, Fujioka, & Fujisawa, 2004;Nagy et al, 1998;Seo & Ko, 2001;Tournaye et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Nonobstructive azoospermia (NOA): could be the consequence of hormonal imbalance [39,40], Y-chromosome deletion or altered karyotype [41,42], long period of toxins exposure [43], chemotherapy or radiation treatment [44], certain medications intake or varicocele [45]. Resurrecting the spermatogenesis process could be achieved depending on the factors inducing azoospermia.…”
Section: Azoospermiamentioning
confidence: 99%
“…Approximately 15-20% of couples in industrialized countries fail to conceive after one year [Boivin et al 2007], and male factor infertility, characterized by semen parameters that fall below the World Health Organization (WHO) [Cooper et al 2010] cut-offs for normozoospermia, is thought to underlie nearly half of these cases [Brugh and Lipshultz 2004]. The most severe form of male infertility, non-obstructive azoospermia (NOA), is defined by the lack of sperm in the ejaculate and very little to no sperm production within the seminiferous tubules [Kumar 2013]. There are many potential causes for NOA, including genetic and congenital abnormalities, post-infectious issues, exposure to gonadotoxins, medications, varicocele, trauma, endocrine disorders, and idiopathic causes [Wosnitzer et al 2014].…”
Section: Introductionmentioning
confidence: 99%